Relationship between the population of mustard aphid, Lipaphis erysimi (Kaltenbach) and weather parameters on different cultivars of Indian mustard (Brassica juncea L.) (The Journal of Plant Protection Sciences, 2020)
The experiments were conducted during rabi season (2007-08 & 2008-09) at Crop Research Centre of G.B. Pant University of Agriculture & Technology, Pantnagar, U.S. Nagar, Uttarakhand to investigate the population dynamics of the mustard aphid, Lipaphis erysimi Kalt. on different 42 cultivars of Indian mustard (B. juncea). The results revealed that the population of L. erysimi exhibited negative correlation with maximum and minimum temperature, rainfall, wind velocity, evaporation and positive with afternoon and morning relative humidity. The values of coefficient of determination (R2) were high (0.92 to 0.99), indicated that the population of L. erysimi governed
Keywords: Correlation; regression; B. juncea; Lipaphis erysimi; weather parameters